PENGARUH PARTISIPASI ANGGARAN TERHADAP SENJANGAN ANGGARAN: KOMITMEN ORGANISASI DAN KETIDAKPASTIAN LINGKUNGAN SEBAGAI VARIABEL MODERATING - Fatmawati, Ifat; Widyaningsih, Aristanti (Program Studi Akuntansi FPEB UPI, 2014)
This research purpose to examine the effect budgetary participation on budgetary slack and moderation organizational commitment and enviroment uncertainty at budget participation on budgetary slack. This research used descriptive verification method. The sampling technique is non probablity sampling withÂ propotional sampling technique. The samples is 142 people from the entire population. The unit of analysis is the head/ field/ sub division in SKPD Serang. data was collected with direct distribution by using numerical scale form ofÂ statement list. The data is processed by using simple regression to test the first hypothesis and regression with the absolute value of the difference for the second and third test hypothesis. The results of this research show; First, there is positive between budgetary participation and budgetary slack. Second, organizational commitment as a moderating variable was not proved to strengthen the influence of budgetary participation on budgetary slack, and third, the uncertainty of the environment as a moderating variable was not proved to strengthen the influence of budgetary participation on budgetary slack